2011
DOI: 10.1523/jneurosci.2057-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Of Notch Activity Promotes Nonmitotic Regeneration of Hair Cells in the Adult Mouse Utricles

Abstract: The capacity of adult mammals to regenerate sensory hair cells is not well defined. To explore early steps in this process, we examined reactivation of a transiently expressed developmental gene, Atoh1, in adult mouse utricles after neomycin-induced hair cell death in culture. Using an adenoviral reporter for Atoh1 enhancer, we found that Atoh1 transcription is activated in some hair cell progenitors (supporting cells) three days after neomycin treatment. By 18 days post-neomycin, the number of cells with Atoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
191
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(205 citation statements)
references
References 62 publications
(89 reference statements)
10
191
2
2
Order By: Relevance
“…Other utricle studies suggested that hair cell damage is required for Notchmediated regeneration in the adult (Wang et al 2010;Lin et al 2011;Jung et al 2013), consistent with what has been shown in the zebrafish lateral line and the FIG. 7.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Other utricle studies suggested that hair cell damage is required for Notchmediated regeneration in the adult (Wang et al 2010;Lin et al 2011;Jung et al 2013), consistent with what has been shown in the zebrafish lateral line and the FIG. 7.…”
Section: Discussionsupporting
confidence: 79%
“…Overall, at P30, there was a 34.1 % loss due to culture, which is consistent with that seen in other adult cultures of vestibular organs (e.g. Lin et al 2011). Generally, this loss appeared as an overall thinning of the hair cell density throughout the sensory epithelium ( Fig.…”
Section: Fig 1 Aa′supporting
confidence: 88%
See 3 more Smart Citations